The Road to Madness : How the 1973-1974 Season Transformed College Basketball - Walker, J. Samuel; Roberts, Randy, 1951- (Book collections on Project MUSE., 2016)
The NCAA men's basketball tournament is one of the iconic events in American sports. In this fast-paced, in-depth account, J. Samuel Walker and Randy Roberts identify the 1973-74 season as pivotal in the making of this now legendary postseason tournament.